Identifikasi Kebutuhan Mahasiswa Terhadap Buku Ajar Manajemen Pendidikan Masyarakat Memuat Soal High Order Thinking Skill - Nengsih, Yanti karmila; Husin, Azizah; Nurrizalia, Mega (Journal of Nonformal Education and Community Empowerment, 2020)
One alternative teaching material that can be used in systematic learning activities is textbooks. This article describes the identification of student needs for textbooks containing High Order Thinking Skill (HOTS) questions. Respondents in this study were students of the educational study program outside the FKIP Sriwijaya University school. The results of the study were obtained from distributing questionnaires using google form and discussed again with the lecturer who teaches community education management courses. The questionnaire for identifying the need for textbooks containing HOTS questions was filled in by 59 students. The data collected through a questionnaire will be analyzed descriptively. The discussion of the research object includes: (1) the principles and material aspects that need to be considered in developing textbooks; (2) the model or approach used that makes it easier for students to understand the subject matter; and (3) display and language used in textbooks. The results showed that: (1) the principles and aspects of the material that need to be considered in developing textbooks include the material that is published in accordance with the learning plan that has been agreed between the lecturer and the student, inserts supporting illustrations of the material, and includes instructions for using the book. teach; (2) textbooks containing HOTS questions are expected to use a group learning and evaluation approach with essay and multiple choice questions; and (3) the display used attracts readers and the language used can be understood by all people.